2020
DOI: 10.1111/emr.12404
|View full text |Cite
|
Sign up to set email alerts
|

Ageing culturally significant relic trees in southeast Queensland to support bushfire management strategies

Abstract: Appropriate fire management strategies are needed to protect forests and large old ecologically and culturally significant trees in natural landscapes. The aim of this study was to determine the age of large old and relic trees of cultural significance that included Cypress Pine (Callitris columellaris F. Muell.), a species that is sensitive to crown scorching fires in a fire-prone landscape, and to calibrate a tree-growth-rate method for estimating tree age. Twelve large trees were dated using radiocarbon ( 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…0.3 ka after dune stabilization due to the presence of ∼1-m-diameter Corymbia intermedia found on the 0.5 ka dune upslope positions that are estimated to be ca. 175-350 yr old (Ngugi et al, 2020; Supplementary Fig. 1a).…”
Section: Implications Of Charcoal Layers In Dune Depositsmentioning
confidence: 99%
“…0.3 ka after dune stabilization due to the presence of ∼1-m-diameter Corymbia intermedia found on the 0.5 ka dune upslope positions that are estimated to be ca. 175-350 yr old (Ngugi et al, 2020; Supplementary Fig. 1a).…”
Section: Implications Of Charcoal Layers In Dune Depositsmentioning
confidence: 99%
“…To establish an age-DBH relationship, we initially explored per annum growth increments and comparisons with related species (Bowman et al 2014). These approaches tended to overestimate tree age (Ngugi et al 2020) and we found this to be the case for Smithton peppermints relative to published ages of other Eucalyptus spp. (Wormington & Lamb 1999;Gibbons et al 2010;Wood et al 2010).…”
Section: Simulation Modelmentioning
confidence: 99%
“…However, such a decline could transform the negative exponential structure into a unimodal or a multimodal distribution over time, which is widely regarded as evidence of a population in decline. Further monitoring of seedlingsapling recruitment dynamics and ageing (Ngugi et al 2020) of tree cohorts to determine recruitment timing, frequency and population trajectory (Ngugi & Neldner 2015) is recommended to inform ongoing management. Further data analyses that use the site-level data to examine mean and variance in size class distributions across the ranges of each species is recommended to facilitate better understanding of differences in demographics across geographic and environmental gradients.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%